Exploring teachers’ strategies in teaching writing for young learners - Hani Elmahida; Desi Prameli Nia; Titik Komariyah (Erudita: Journal of English Language Teaching, 2021)
Teaching writing for young learners (YL) needs unique strategies from each teacher. The purpose of this study is to help teachers explore strategies for teaching writing for young learners. The survey was used with a descriptive-qualitative method which was carried out by giving an open-ended questionnaire to five English teachers and tutors from a different institution. Then, the most appropriate strategy could not be generalized because there are different conditions of students' and teachers’ qualifications. However, teachers must pay attention to three aspects of teaching such as understanding the characteristics of students, developing fun ways of learning, and peer feedback strategies. Teachers must be able to evaluate whether or not the strategy they provide can produce good results. From this research, with the exploring three different teachers' strategies in teaching writing, most of the students have succeeded in the minimum passing grade in each class. Furthermore, this paper pursued teachers to be able to design teaching writing for young learners in the right ways.